2018
DOI: 10.1002/cam4.1670
|View full text |Cite
|
Sign up to set email alerts
|

Iron overloaded polarizes macrophage to proinflammation phenotype through ROS/acetyl‐p53 pathway

Abstract: PurposeMacrophages play critical roles in inflammation and wound healing and can be divided into two subtypes: classically activated (M1) and alternatively activated (M2) macrophages. Macrophages also play important roles in regulating iron homeostasis, and intracellular iron accumulation induces M1‐type macrophage polarization which provides a potential approach to tumor immunotherapy through M2 tumor‐associated macrophage repolarization. However, the mechanisms underlying iron‐induced M1 polarization remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
134
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(152 citation statements)
references
References 23 publications
9
134
0
Order By: Relevance
“…These findings are also in agreement with recent findings suggesting a double-faced response of cell-mediated immunity in β-TM patients, namely that T cells show a stimulated phenotype while in fact their activity is suppressed [65]. As described in the Introduction, IO is associated with immune-inflammatory responses, M1 macrophage polarization and increased TNF-α expression due to IO and antigenic stimulation induced by chronic transfusion therapy [18][19][20] The fourth major finding of this study is that MDD in β-TM is characterized by increased levels of IL-1β and M1 activation as compared with β-TM patients without MDD and that the M1/CIRS ratio was significantly increased in β-TM with MDD versus controls while those with β-TM without MDD occupied an intermediate position. Moreover, the CDI score was significantly associated with both pro-inflammatory cytokines, the M1 macrophage activation index and the M1/CIRS ratio.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are also in agreement with recent findings suggesting a double-faced response of cell-mediated immunity in β-TM patients, namely that T cells show a stimulated phenotype while in fact their activity is suppressed [65]. As described in the Introduction, IO is associated with immune-inflammatory responses, M1 macrophage polarization and increased TNF-α expression due to IO and antigenic stimulation induced by chronic transfusion therapy [18][19][20] The fourth major finding of this study is that MDD in β-TM is characterized by increased levels of IL-1β and M1 activation as compared with β-TM patients without MDD and that the M1/CIRS ratio was significantly increased in β-TM with MDD versus controls while those with β-TM without MDD occupied an intermediate position. Moreover, the CDI score was significantly associated with both pro-inflammatory cytokines, the M1 macrophage activation index and the M1/CIRS ratio.…”
Section: Discussionsupporting
confidence: 91%
“…Intracellular iron accumulation may induce M1 macrophage polarization [19] and increased inflammatory gene expression [20].…”
Section: Introductionmentioning
confidence: 99%
“…Heme uptake by macrophages in the damaged spinal cord promotes M1driven inflammation in mice, 38 whereas iron sequestration induced an M1 phenotype in raw246.7 macrophages. 39 It has even been suggested that sustained, iron-induced, proinflammatory macrophages may contribute to delayed healing by triggering fibroblast senescence. 40,41 On the contrary, in atherosclerotic plaques, hemoglobinhaptoglobin complexes shifted macrophages toward an M2 state both in vivo (higher CD163) and in vitro (increased IL-10 and IL-1RA 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that increasing miR-216a through indirect means could be exploited therapeutically, in ovarian cancer. Reactive oxygen species (ROS) polarize macrophages to M1-like phenotypes [ 43 , 44 ]. HOXA9 polarizes peritoneal macrophages to M2-like phenotypes [ 45 ].…”
Section: Bipolar Macrophagesmentioning
confidence: 99%